Cellular senescence as a key player in chronic heart failure pathogenesis: Unraveling mechanisms and therapeutic opportunities - Zhao, Shuqing; Zhang, Yu; Zhao, Ying; Lu, Xiaohui (Progress in biophysics and molecular biology, 2025)
Chronic heart failure (CHF) is the final stage of heart disease and is caused by various factors. Unfortunately, CHF has a poor prognosis and a high mortality rate. Recent studies have found that aging is a significant risk factor for the development of CHF and that cellular senescence plays a vital role in its development. This article reviews different types of cellular senescence, mitochondrial dysfunction in senescent cells, autophagy in senescent cells, and senescence-associated secretory phenotype (SASP), and epigenetic regulation, to provide new perspectives on the research and treatment of CHF. •Aging is a key risk factor for chronic heart failure, with cellular senescence driving its progression.•Reviews cellular senescence's role in chronic heart failure pathogenesis and potential therapies.•Covers senescence in cardiac cells (progenitor, cardiomyocyte, endothelial, fibroblast, immune) and key mechanisms.•Targeting senescence-related pathways offers novel therapeutic strategies for chronic heart failure.